2021
DOI: 10.1590/1516-4446-2020-0864
|View full text |Cite
|
Sign up to set email alerts
|

Stigma toward individuals with mental disorders among Brazilian psychiatrists: a latent class analysis

Abstract: Objective: The stigma toward individuals with mental disorders is highly prevalent, not only in the general population but among health care providers as well. The aim of this study was to identify subgroups based on stigmatizing beliefs related to psychiatric disorders among Brazilian psychiatrists, as well as to investigate their association with clinical and personality characteristics. Methods: Latent cluster analysis was used to find subgroups of cases in multivariate data according to a psychotic (schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
5
1
1
Order By: Relevance
“…For instance, the following statements from the English-language guidelines "The first aider should be open to any opportunity that presents itself to talk about their concerns with the person" and "The first aider should know that allowing the person to talk about how they are feeling can help them feel better, not worse" received low ratings by both panels. This may be because mental health problems are stigmatized in Brazil [11], even among mental health professionals [31], and talking openly about a mental health problem may be considered demeaning to a person with depression in Brazil. Furthermore, statements related to the first aider prioritizing the person's safety above all were seen in the Brazilian adapted guidelines.…”
Section: Comparison With the English-language Guidelinesmentioning
confidence: 99%
“…For instance, the following statements from the English-language guidelines "The first aider should be open to any opportunity that presents itself to talk about their concerns with the person" and "The first aider should know that allowing the person to talk about how they are feeling can help them feel better, not worse" received low ratings by both panels. This may be because mental health problems are stigmatized in Brazil [11], even among mental health professionals [31], and talking openly about a mental health problem may be considered demeaning to a person with depression in Brazil. Furthermore, statements related to the first aider prioritizing the person's safety above all were seen in the Brazilian adapted guidelines.…”
Section: Comparison With the English-language Guidelinesmentioning
confidence: 99%
“…Moreover, these demographics face additional risks including metabolic syndrome, diabetes, sedentary lifestyles, and smoking. Often, they lack preventive care, partly attributable to inadequate health education and pervasive stigmatization [14,15]. The diagnosis further limits their access to regular medical care.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Psychiatrists who had regular contact with people with mental illness in their community showed more favourable attitudes toward them. 8 , 11 However, a large study among psychiatrists showed that close relationships or frequent contact with affected family members could result in more stigma than infrequent contact. 11 …”
Section: Introductionmentioning
confidence: 99%
“…8 , 11 However, a large study among psychiatrists showed that close relationships or frequent contact with affected family members could result in more stigma than infrequent contact. 11 …”
Section: Introductionmentioning
confidence: 99%